PERBEDAAN PEMBELAJARAN MENGGUNAKAN APLIKASI MULTIMEDIA PRESENTASI DENGAN PEMBELAJARAN MEDIA PROGRAM PENGOLAH KATA TERHADAP HASIL BELAJAR MATA PELAJARAN TEORI KEJURUAN TEKNIK FURNITUR - Hadi Mukhlish; Tuti Iriani; R Eka Murtinugraha (LPPM Universitas Negeri Jakarta, 2012)
The aims of this research is obtaining the empirical data about the difference of learning output of the students who are taught using Microsoft PowerPoint for experimental class and using Microsoft Wordfor control class at the subject: Vocational Furniture in SMK Negeri 52 Jakarta. The observation time starts from November 2010 until December 2010. The method used in this research is experimental method. A number of 180 students from the 11th grade students of SMKN 52 Jakarta are populated to be the subject of the experiment where thepurposive sampling is applied. The XI TKF A consists of 15 students is grouped as the control class and the XI TKF B consists of 15 students is grouped as the experimental class. The instrument of research is in the format of test results; the 1st – 3rd test makes use of the essay problems consisted of 5 problems at the end of the meeting either for the control class or experimental class, otherwise the multiple choice problems are applied for the 4th test consisted of 25 problems. The item validity test and reliability test are treated before the instrument is used. It shows that 20 instruments is valid whereas the other 5 problems is invalid in the 4th test with the reliability index 0.802. Since the reliability index is high, so the 25-multiple-choice-problem is insisted to be run as the research instrument. Normality test and homogeneity test are chosen as the analytical requirement test. The results from the sampling data show that it is normally distributed and homogeneous. While, the hypothesis is tested.